Comparison of foreign and domestic IPO firms in Singapore. - Goh, Weisheng. (2008)
This study compares the overall performance between foreign and domestic IPOs in Singapore. Foreign firms on average have better operating performance before and after listing, especially those from China. Initial share price returns for domestic IPOs are higher, suggesting higher under-pricing. Conversely, subsequent share returns for foreign firms are higher.